PENGARUH PERSEPSI SISWA MADRASAH ALIYAH TENTANG PENGHAPUSAN MATERI JIHAD PADA MATA PELAJARAN FIQH TERHADAP PEMAHAMAN SISWA TENTANG JIHAD - Syihabuddin, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2021)
By removing and revising and replacing Islamic teachings on Jihad and the Caliphate, it will alienate generations of people and they will become phobic towards the teachings of their own religion. Moreover, leading to the opinion that Jihad and the caliphate are no longer relevant to the current context. Even though the khilafah is the solution to solve the problems of life today. So it is very wrong if Islamic teachings should be revised or moderate its teachings. This massive, structured moderation step is absolutely useless. In fact, it will bring this ummah to be increasingly radicalized secular mind. Increasingly want to get away from Islamic law. Because it should be stopped or Allah SWT will remind you in His way. The purpose of this study was to determine the effect of students 'perceptions of Madrasah Aliyah about the elimination of Jihad material on the subject of fiqh on students' understanding of jihad. The method suitable for use in this research is descriptive method with a quantitative approach. The research sample consisted of 172 respondents. Data analysis using inferential. The simple correlation technique used is Product Moment. Based on the data analysis, it was concluded that there was an influence on students 'perceptions of Madrasah Aliyah about the elimination of Jihad material in the subject of fiqh on students' understanding of jihad. This is indicated by the results of the correlation significance test showing that t> t table (13.68> 1.974). Thus the research hypothesis which states that there is an influence on the perceptions of Madrasah Aliyah students about the elimination of Jihad material on the subject of fiqh on students' understanding of jihad has been tested.